Characteristics and Antioxidant Stability of Red Fruit (Pandanus conoideus Lam) Protein Based Microcapsule - Yanuar, Willy; Widjanarko, Simon Bambang; Wahono, Tri (Jurnal Teknologi Pertanian, 2007)
Red fruit can commercially be obtained in extract (oil) form and capsulated oil (softcapsule). Within oil form, this product has lower tenacity and stability against light, heat, oxygen, and extreme environmental condition due to its content of easily degradable antioxidant group active compound. Red Fruit based essence product have been ever fortified into other food product, but only fortified into fried oil to improve carotene rate. One alternative to deal this problem refers to microencapsulation. Microencapsulation means the process of wrapping one certain central particle with other material to reach expected physical and chemical characteristic. Microencapsulation method used in this research has been spray drying.Â Research was arranged by using Completely Randomized Design that organized in factorial pattern involving two factors. First factor includes coating materials (soybean protein isolate and Na-caseinate), while second factor entails red fruit oil proportion (20 %, 30%, and 40%). The analysis covers moisture content, Î²-carotene, microstructure, microencapsulation efficiency, yield, antioxidant activity, and microcapsule stability against temperature.Â Results of analysis indicate that microcapsule with Na-caseinate had better quality compared to wrapping with soybean protein isolate. The best treatment comes from treatment combination with Na-caseinate wrapping in proportion of 20% red fruit oil. Microcapsule with the best treatment has moisture content of 1.34 %, Î²-carotene of 580.42 Î¼g/g, microcapsule size of 36,98 Î¼m, microencapsulation efficiency of 95,59%, and yield of 93,37%. The process of red fruit oil microencapsulation with Na-caseinate in proportion of 20 % can be used as an alternative to facilitate distribution process, to increase product storability, and product fortification process into other food product.Keywords: microencapsulation, red fruit, oil proportion, antioxidant stability, protein based coating